Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1080/08897077.2019.1680479
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Technological Solutions for Overdose Monitoring: Perspectives of People who use Drugs

Abstract: Introduction Rising overdose deaths are a devastating problem across the United States and Canada. Despite the availability of observed consumption sites in British Columbia (BC), data suggest people who use drugs (PWUD) alone in private residences are most at risk of overdose death. These individuals may not use consumption sites due to fear of stigmatization, lack of privacy, or personal preference. It is this population that would benefit from overdose monitoring alternatives. Methods This 2018 study employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(76 citation statements)
references
References 26 publications
5
68
0
1
Order By: Relevance
“…A previous study conducted by Small et al [ 21 ] showed that one of the factors PWUD take into consideration in their choice of environment is protection from law enforcement and from potential street violence or harassment, which impacts their comfort or anxiety level [ 21 ]. Individuals may also have specific rituals and preferences that influence their environment of choice when using substances [ 22 ]. Additionally, some participants’ responses implied that they had no alternative but to use alone.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous study conducted by Small et al [ 21 ] showed that one of the factors PWUD take into consideration in their choice of environment is protection from law enforcement and from potential street violence or harassment, which impacts their comfort or anxiety level [ 21 ]. Individuals may also have specific rituals and preferences that influence their environment of choice when using substances [ 22 ]. Additionally, some participants’ responses implied that they had no alternative but to use alone.…”
Section: Discussionmentioning
confidence: 99%
“…While 67.4% of participants that reported using alone had a naloxone kit, the opportunity to respond may not be possible if using alone. However, some PWUD may inform friends or neighbours they are going to use, leave their door unlocked, and ask that they check on them [ 22 ]. Similarly, McLean details occurrences of people who ‘overdosed while using alone, yet were saved by friends or family who were somehow alerted to the danger’, such as hearing a thud [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While our participants agreed that improved access to overdose response was crucial for their survival, they expressed hesitation to use these services if calling 911 was the policy in the event of an overdose. In addition, mobile apps come with distinct limitations such as accessibility concerns and general technology barriers [45].…”
Section: Discussionmentioning
confidence: 99%